Implementing Model-Based Variable-Structure Controllers For Robot Manipulators With Actuator Modelling - Tso, S. K.; Law, P.L; Xu, Y.; Shum, H. Y. (1993)
A model-based control scheme for robot manipulators employing a variable structure control law has previously been found to perform well parameters are carefully chosen model of this original scheme which the actuator dynamics is taken into consider The practical experiments are carried out on a commerci revolute-joint robot manipulator.